The The Implementation of Experiential Model of Exploring the Surroundings in Learning to Write Poetry based on Students' Learning Motivation - Pangestuti, Aulia Khaerunisa; Zulaeha, Ida; Haryati, Nas (Journal of Research and Educational Research Evaluation, 2022)
The use of the EJAS (Experiental Jelajah Alam Sekitar/ Experiental of Exploring the Surroundings) model in learning to write poetry is designed as an alternative to a more meaningful learning process. The EJAS model helps students express their experiences of exploring the environment and being creative in the form of poetry. The purpose of this study was to evaluate the use of the EJAS model in learning to write poetry based on students' learning motivation. This study used an experimental research method with a factorial design. Data was collected using test techniques to determine learning outcomes and non-test techniques to determine the level of learning motivation. The data were tested and processed using statistical tests, then analyzed using quantitative descriptive methods. The data was processed and tested using the SPSS application. The results of the study using the paired samples test showed a significance value of 0.000 <0.05. There was a difference in the average learning outcomes of students, the results of the initial test showed an average grade of 64.13 and the average result of the final test was 81.04. Based on the test results, it could be concluded that the EJAS model was effectively used in learning to write poetry. The EJAS model which was usually used in biology learning can improve students' skills, creativity, and motivation in learning to write poetry.